Twoplex 12/13C6 aniline stable isotope and linkage‐specific sialic acid labeling 2D‐LC‐MS workflow for quantitative N‐glycomics. Issue 1 (January 2017) - Albrecht, Simone; Mittermayr, Stefan; Smith, Josh; Martín, Silvia Millán; Doherty, Margaret; Bones, Jonathan
Abstract : Quantitative glycomics represents an actively expanding research field ranging from the discovery of disease‐associated glycan alterations to the quantitative characterization of N ‐glycans on therapeutic proteins. Commonly used analytical platforms for comparative relative quantitation of complex glycan samples include MALDI‐TOF‐MS or chromatographic glycan profiling with subsequent data alignment and statistical evaluation. Limitations of such approaches include run‐to‐run technical variation and the potential introduction of subjectivity during data processing. Here, we introduce an offline 2D LC‐MS E workflow for the fractionation and relative quantitation of twoplex isotopically labeled N ‐linked oligosaccharides using neutral 12 C6 and 13 C6 aniline (Δmass = 6 Da). Additional linkage‐specific derivatization of sialic acids using 4‐(4, 6‐dimethoxy‐1, 3, 5‐trizain‐2‐yl)‐4‐methylmorpholinium chloride offered simultaneous and advanced in‐depth structural characterization. The potential of the method was demonstrated for the differential analysis of structurally defined N ‐glycans released from serum proteins of patients diagnosed with various stages of colorectal cancer. The described twoplex 12 C6 / 13 C6 aniline 2D LC‐MS platform is ideally suited for differential glycomic analysis of structurally complex N ‐glycan pools due to combination and analysis of samples in a single LC‐MS injection and the associated minimization in technical variation.